2022
DOI: 10.1021/acs.macromol.1c02325
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Functionalized Poly(ε-caprolactone); Chain Polymerization Followed by Polycondensation in One Pot with Initiator and Catalyst in One Molecule. Synthesis and Molecular Structures

Abstract: Poly(ε-caprolactone) and polylactide are biocompatible and biodegradable polymers. Both are hydrophobic, and their backbones do not contain reactive groups. The existing methods of functionalization are mostly based on copolymerization with functional comonomers that require additional syntheses. In the method of functionalization described in this work, special end groups are introduced that allow, after chain polymerization of ε-caprolactone (CL), the following step, in one pot, namely polycondensation. Chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…92 In the literature functionalization of PCL with polylactide using hydromethyl phosphonic acid as the catalyst, which added end groups required for polycondensation, this lead to the formation of macromolecules with acidic groups. 93 PCL-PEG-PCL triblock copolymers are also synthesized by ROP using DPP as catalyst. 94 Amokrane et al used UV radiation to graft poly (sodium styrene sulfonate) (polyNaSS) on PCL this involved oxidation of PCL surface followed by submersion in NaSS.…”
Section: Functionalized Pclmentioning
confidence: 99%
See 1 more Smart Citation
“…92 In the literature functionalization of PCL with polylactide using hydromethyl phosphonic acid as the catalyst, which added end groups required for polycondensation, this lead to the formation of macromolecules with acidic groups. 93 PCL-PEG-PCL triblock copolymers are also synthesized by ROP using DPP as catalyst. 94 Amokrane et al used UV radiation to graft poly (sodium styrene sulfonate) (polyNaSS) on PCL this involved oxidation of PCL surface followed by submersion in NaSS.…”
Section: Functionalized Pclmentioning
confidence: 99%
“…Some of the possible methods of functionalization are modifying the polymer back bone, polymerization of functionalized monomers, or copolymerization with other monomers 92 . In the literature functionalization of PCL with polylactide using hydromethyl phosphonic acid as the catalyst, which added end groups required for polycondensation, this lead to the formation of macromolecules with acidic groups 93 . PCL‐PEG‐PCL triblock copolymers are also synthesized by ROP using DPP as catalyst 94 .…”
Section: Biological Properties Of Pclmentioning
confidence: 99%
“…have shown that hydroxymethyl phosphonic acid can act as a catalyst and initiator of the ROP of ε-caprolactone (εCL) with the formation of εCL oligomers containing reactive groups on both ends of the macromolecule. Very recently they demonstrated that these oligomers can be subjected to polycondensation at 100–110 °C with a formation of PCPAs ( M n up to 25 kDa) ( Scheme 8 ) with mostly linear microstructure ( 31 P NMR data) [ 60 ].…”
Section: Design and Synthesis Of Polyphosphodiestersmentioning
confidence: 99%
“…PCL: polycaprolactone: (C 6 H 10 O 2 ) n PCL is a caprolactone polymer with a molecular weight of more than 25 000 and is a biodegradable thermoplastic resin with a relatively low melting temperature (60 °C), which can be obtained by polymerizing 3-polycaprolactone. 25,26 Owing to the high heat stability and low melting temperature of PCL, thermal decomposition and hydrolysis are not serious problems in the extruder, making PCL suitable for the production of lms, sheet molding, injection molding, and yarning. Attempts have been made to utilize PCL for the production of agricultural lms and compost bags, as well as glue, because of its high adhesion property due to its high crystallinity.…”
Section: Pva: Polyvinyl Alcohol: [Ch 2 Ch(oh)] Nmentioning
confidence: 99%